To Practice What You Preach : Sweden's Feminist Foreign Policy in Diplomatic Work - Rosén Sundström, Malena; Elgström, Ole (Feminist Climate Policy in Industrialised States : A Gender-Just Climate Emergency Response, 2025)
Between 2014 and 2022, Sweden introduced a feminist foreign policy (FFP), which entailed a “systematic gender equality perspective throughout foreign policy”. This chapter focuses on how FFP was practiced and implemented by officials at Swedish Embassies around the world. Using a framework of practice theory, implementation theory and feminist institutionalism, the overarching questions guiding the study concern how FFP was conducted in diplomatic work and to what extent it was implemented. Based on in-depth interviews, the main findings are that: 1) the FFP demonstrated a relatively high degree of successful implementation 2) the implementation of the policy was guided by a pragmatic approach: the word “feminism” was not always used, rather, the content of the policy mattered more than the packaging and 3) the practice of FFP was very sensitive to context, with the effect that different aspects of FFP were in focus in different locations. Sweden’s previous work on gender equality in foreign policy helped officials to adjust their practices to the more ambitious framework of FFP. Based on our research on Sweden’s FFP, we argue that that a feminist agenda, such as a feminist climate policy, can be put into practice, if the political will exists, if clear goals and instruments for a well-structured implementation process are provided and if those “doing” the policy on the ground are closely involved in the process.